2008
DOI: 10.1007/s10620-008-0389-5
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of Histogenesis of Gastric Carcinomas: A Comparative Histopathological Study Between Helicobacter pylori-Negative and H. pylori-Positive Cases

Abstract: We histopathologically re-evaluated the histogenesis of gastric carcinomas from comparative studies between Helicobacter pylori-positive and H. pylori-negative cases using the gastritis score from the Updated Sydney System. The incidence of H. pylori-negative gastric carcinomas was 3.11% (12/386); they are likely to develop in the fundic gland mucosa, and show a gastric phenotype by mucin immunohistochemistry. Even in cases of completely gastric and predominantly gastric phenotypes, CDX2 protein was expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 26 publications
1
56
3
Order By: Relevance
“…H. pylori positivity in the general population as well in gastric cancer patients is very high in Japan and in countries with a high incidence of gastric cancer. [19][20][21]29 It is interesting to note that in gastric cancer patients, very low positivity rates of H. pylori infection have been reported from the US, [30][31][32][33] and clinical studies demonstrated clearly lower survival rates when compared with Japanese patients at the same stages of disease. 34 Differences in prognosis between Eastern and Western series have been explained on the basis of different surgical approaches, less advanced stage of disease, and more careful tumor staging 35 ; the association with H. pylori status may shed more light on geographic variability in the prognosis of patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori positivity in the general population as well in gastric cancer patients is very high in Japan and in countries with a high incidence of gastric cancer. [19][20][21]29 It is interesting to note that in gastric cancer patients, very low positivity rates of H. pylori infection have been reported from the US, [30][31][32][33] and clinical studies demonstrated clearly lower survival rates when compared with Japanese patients at the same stages of disease. 34 Differences in prognosis between Eastern and Western series have been explained on the basis of different surgical approaches, less advanced stage of disease, and more careful tumor staging 35 ; the association with H. pylori status may shed more light on geographic variability in the prognosis of patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are distinct types of IMs, not all carrying definitive preneoplastic potential, and some authors have argued that IM in general is a paraneoplastic condition because the earliest gastric carcinomas arise from gas-tric, not intestinalized, glands. [5][6][7][8][9][10] Also, traditional models do not take into account that atrophy of the corpus is almost always concomitant with pseudopyloric or spasmolytic polypeptide expressing metaplasia (SPEM; see below) 11,12 and neglects evidence that this type of metaplasia may have closer links to eventual development of dysplasia or carcinoma. 13 Recently, mouse models have argued for even more unexpected routes to the development of cancer, with a critical role of transdifferentiation of gastric epithelial cancer progenitors from migrating mesenchymal stem cells.…”
mentioning
confidence: 99%
“…Whereas some studies showed that patients with HPNGC had higher proportion of the proximal tumor location, more diffuse histologic type and younger age of disease onset as compared to those of HPPGC [14][15][16][17], other studies failed to show the associations. The contradictory results might be attributed to the differences in the prevalence of H. pylori infection in the countries where these studies were conducted [15,18,19]. Another explanation might be the different definitions of H. pylori negative status in patients with gastric cancer, especially for those with coexisting atrophic gastritis.…”
Section: Introductionmentioning
confidence: 99%